Emotion Reinforced Visual Storytelling - Li, Nanxing; Liu, Bei; Han, Zhizhong; Liu, Yu-Shen; Fu, Jianlong (ICMR, 2019)
Automatic story generation from a sequence of images, i.e., visual storytelling, has attracted extensive attention. The challenges mainly drive from modeling rich visually-inspired human emotions, which results in generating diverse yet realistic stories even from the same sequence of images. Existing works usually adopt sequence-based generative adversarial networks (GAN) by encoding deterministic image content (e.g., concept, attribute), while neglecting probabilistic inference from an image over emotion space. In this paper, we take one step further to create human-level stories by modeling image content with emotions, and generating textual paragraph via emotion reinforced adversarial learning. Firstly, we introduce the concept of emotion engaged in visual storytelling. The emotion feature is a representation of the emotional content of the generated story, which enables our model to capture human emotion. Secondly, stories are generated by recurrent neural network, and further optimized by emotion reinforced adversarial learning with three critics, in which visual relevance, language style, and emotion consistency can be ensured. Our model is able to generate stories based on not only emotions generated by our novel emotion generator, but also customized emotions. The introduction of emotion brings more variety and realistic to visual storytelling. We evaluate the proposed model on the largest visual storytelling dataset (VIST). The superior performance to state-of-the-art methods are shown with extensive experiments.